Simple method for preparing polymer long-acting protected perovskite quantum dots

By using the polymer of the carboxyl and amino seal as a protective agent, combined with the method of high temperature and high pressure water thermal reaction method, the polymer long -acting and stable perovskite quantum dots are prepared to solve the problem of cumbersome and stable process in the existing technology. Efficient and stable perovskite quantum dots are prepared.

CN119371966APending Publication Date: 2025-01-28HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411504012.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The process of improving the stability of perovskite quantum dots in the prior art is cumbersome, with poor long-term stability, and the polymer is not grafted on the surface of quantum dots and has a low grafting rate.

Method used

The polymer with the carboxyl and amino seal is used as a protective agent. It is mixed with halogen, carbonate, and olefin solvents, and then reaches the hydrophilic response at a high temperature and high -pressure environment to obtain the perovskite quantum point protected by the polymer.

Benefits of technology

A simple operation and long -term polymer with a long -term and stable parts of olty ore ore are preparation, which improves the stability of the quantum dot and the tolerance of high temperature, high humidity environment and polar solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371966A_ABST
    Figure CN119371966A_ABST
Patent Text Reader

Abstract

The invention discloses a simple method for preparing a polymer long-acting protected perovskite quantum dot, which is characterized in that a carboxyl and amino (one or both included) terminated polymer is used as a ligand to directly participate in synthesis of the quantum dot, and the polymer grafting density is improved so as to improve the tolerance of the quantum dot to adverse conditions such as high humidity, high temperature, polar solvents and the like. The method comprises the following steps: heating and stirring the end-capped polymer, lead halide, cesium carbonate and other reagents to obtain a precursor solution, transferring the precursor solution into a high-pressure reaction kettle, reacting for a certain time, and cooling to room temperature to obtain the perovskite quantum dots with long-acting protection of the polymer. The method is easy to operate and high in repeatability, and halide perovskite quantum dots of different sizes and materials can be prepared; the application range is wide, and the method is suitable for various end-capped polymers containing one or both of carboxyl and amino. The obtained perovskite quantum dot has relatively high environmental tolerance and fluorescence quantum yield, and can be used in the fields of fluorescence imaging, photoelectric conversion materials, display materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to polymer / The field of inorganic nanocomposites, and more specifically, to a simple method for preparing perovskite quantum dots with long-term protection by polymers. Background Art

[0002] Perovskite is a type of ceramic oxide named after the Russian geologist Lev Perovski. This type of oxide was first discovered in calcium titanate (CaTiO3) compounds in perovskite, hence the name. Its general chemical formula is ABX3. Among them, halide perovskite quantum dots have been widely used in lighting, display, solar cells, etc. due to their excellent high luminescence yield, luminescence purity and wide emission spectrum, and are favored by researchers. However, perovskite quantum dots have poor stability, are highly sensitive to high temperature, high humidity environment and polar solvents, are prone to fluorescence quenching, lose their effectiveness, and hinder their application development. Therefore, finding a method to improve perovskite quantum dots is an important research direction in this field. At present, the mainstream methods for improving the stability of perovskite nanocrystals include surface passivation, metal ion doping, physical coating and ligand protection. Among them, the use of polymers as protective ligands can not only improve the stability of nanoparticles, but also improve the compatibility of perovskite quantum dots with polymer substrates, which has obvious advantages in the preparation of flexible functional devices. However, this type of method generally has a complicated process, and the efficiency of polymer grafting on the surface of quantum dots is not high, the grafting rate is low, and the improvement in stability is limited. Summary of the invention

[0003] In view of the defects and improvement needs in the above-mentioned prior art, the present invention provides a preparation method with simple operation. A polymer terminated with a carboxyl group or an amino group (one of the two, or both) is used as a protective agent to replace the small molecule compounds oleic acid and oleylamine in the traditional method, and is mixed with lead halide, cesium carbonate and an olefin solvent, heated and stirred, and then transferred to a reactor to react under a high temperature and high pressure environment, and cooled to room temperature after the reaction is completed. Polymer-protected perovskite quantum dots can be obtained by adding a non-polar solvent. Thereby solving the problem of cumbersome process steps and poor long-term stability in the existing method for improving the stability of perovskite quantum dots.

[0004] To achieve the above object, according to one aspect of the present invention, a simple method for preparing perovskite quantum dots with long-term polymer protection is provided, comprising the following steps:

[0005] (1) Preparation of precursor solution: terminal functionalized polymer is mixed with lead halide (PbX2, X = Br, Cl, I), cesium carbonate CsCO3, and olefin, and then heated and stirred to obtain a precursor solution of perovskite.

[0006] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) is transferred to a hydrothermal reactor, and the reaction is continued for a period of time under high temperature and high pressure. After the reaction is completed, the solution is cooled to room temperature. A non-polar solvent is added to obtain polymer-protected perovskite quantum dots.

[0007] Preferably, the terminal functionalized polymer in step (1) contains a carboxyl group (-COOH) or an amino group (-NH2), or both, at its terminal.

[0008] Preferably, the molecular weight of the polymer in step (1) is 500 to 1,000,000 g / mol.

[0009] Preferably, the solvent in step (1) is an olefin organic compound.

[0010] Preferably, the heating and stirring temperature in step (1) is 100-300°C.

[0011] Preferably, the heating and stirring time in step (1) is 5 to 30 minutes.

[0012] Preferably, the reaction temperature in step (2) is 120-260°C.

[0013] Preferably, the reaction time in step (2) is 30 to 60 minutes.

[0014] Preferably, the non-polar solvent added in step (3) is selected from the group consisting of n-hexane, cyclohexane, petroleum ether, carbon disulfide, dichloromethane, chloroform, toluene, benzene, ethyl acetate, dioxane, and tetrahydrofuran.

[0015] According to another aspect of the present invention, a long-lasting and stable polymer perovskite quantum dot is provided, which has a fluorescence intensity drop of 0-50% when stored at room temperature for 60 days, or immersed in a polar solvent (such as water, ethanol, etc.) for 15 days, or placed in a high temperature environment of 100°C for 30 days; it can be evenly dispersed in a polymer substrate without local agglomeration. The self-assembly property can be used to prepare a self-supporting ordered array film, or it can be mixed with other polymers and assembled into an ordered structure material; it can be used in photovoltaic power generation, lasers, fluorescence imaging, light-emitting diodes and other fields.

[0016] In general, compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects.

[0017] (1) The present invention uses a polymer terminated with a carboxyl group or an amino group (one of the two or both) instead of oleic acid or oleylamine as a protective agent, and after being evenly mixed with lead halide (PbX2, X = Br, Cl, I), cesium carbonate and an olefin solvent, a long-lasting and stable polymer perovskite quantum dots are prepared by a one-step method.

[0018] (2) The perovskite quantum dots prepared by the present invention have high fluorescence quantum yield, long-term storage stability, and tolerance to high temperature, high humidity environment and polar solvents.

[0019] (3) The perovskite quantum dots prepared in the present invention have good compatibility with polymer flexible materials and can be evenly dispersed in the substrate to avoid local agglomeration.

[0020] (4) The perovskite quantum dots prepared in the present invention can utilize their self-assembly characteristics to prepare self-supporting ordered array films.

[0021] (5) The perovskite quantum dots prepared by the present invention have enhanced performance in various aspects and will be more suitable for applications in photovoltaic power generation, lasers, fluorescence imaging, light-emitting diodes and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the process of a simple method for preparing perovskite quantum dots with long-term protection by polymers;

[0023] Figure 2 It is the transmission electron microscope image and X-ray diffraction spectrum of the perovskite quantum dots with long-term protection by the polymer obtained in Example 1;

[0024] Figure 3 These are digital photos of the perovskite quantum dots protected by the polymer long-term obtained in Example 1 after being stored at room temperature for 60 days, immersed in a polar solvent (water) for 15 days, and placed in a high temperature environment of 100° C. for 30 days.

[0025] Figure 4 These are digital pictures of the composite film prepared by blending the perovskite quantum dots with long-term polymer protection obtained in Example 1 with a polymer substrate under sunlight and ultraviolet light. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation cases. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] The present invention provides a simple method for preparing polymerized long-lasting stable perovskite quantum dots, comprising the following steps:

[0028] (1) Preparation of precursor solution: terminal functionalized polymer is mixed with lead halide (PbX2, X = Br, Cl, I), cesium carbonate CsCO3, and olefin solvent, and then heated and stirred for a period of time to obtain a precursor solution of perovskite.

[0029] The terminal functionalized polymer has a carboxyl group (-COOH) or an amino group (-NH2), or both, at its terminal, and a molecular weight of 500 to 1,000,000 g / mol; the solvent is an olefin organic compound; the heating and stirring temperature is 100 to 300° C.; and the heating and stirring time is 5 to 30 minutes.

[0030] The specific operation of the experiment is as follows: the polymer, lead halide, cesium carbonate, and olefin solvent are added to a round-bottom flask, heated and stirred in an oil bath, and reacted for 10 minutes to make them evenly mixed.

[0031] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) is transferred to a hydrothermal reactor, and the reaction is continued for a period of time under high temperature and high pressure. After the reaction is completed, the solution is cooled to room temperature. A non-polar solvent is added to obtain polymer-protected perovskite quantum dots.

[0032] The reaction temperature is 120-260° C., the reaction time is 30-60 minutes, and the non-polar solvent is selected from n-hexane, cyclohexane, petroleum ether, carbon disulfide, dichloromethane, chloroform, toluene, benzene, ethyl acetate, dioxane, and tetrahydrofuran.

[0033] The present invention can realize a simple method to prepare long-term stable polymerized perovskite quantum dots, and the key is to use terminal functionalized polymers to replace oleic acid and oleylamine. The polymer terminal should contain a carboxyl group (-COOH) or an amino group (-NH2), or both. The coordination of the carboxyl group and the amino group with the lead ion and the cesium ion is utilized to connect the perovskite quantum dots to the perovskite quantum dots in the early stage of their formation, so that the grafting density is improved compared with the ligand exchange method used in the post-modification. The increase in grafting density can form a protective layer on the surface of the quantum dots, thereby improving the tolerance of the quantum dots to high temperature, high humidity environment and polar solvents.

[0034] The perovskite quantum dots can be successfully prepared according to this method, which is simple to operate and highly repeatable, and is applicable to different halide perovskite quantum dots, such as cesium lead bromide, cesium lead chlorine, cesium lead iodine, etc., as well as different types of polymers.

[0035] The following are examples:

[0036] Example 1

[0037] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0038] (1) Preparation of precursor solution: Carboxyl-terminated polystyrene with a molecular weight of 500 g / mol, lead bromide (PbBr2), cesium carbonate (CsCO3), oleylamine, and 1-octadecene were added to a round-bottom flask, heated to 120°C in an oil bath, and stirred for 20 minutes to mix evenly to obtain a precursor solution of perovskite.

[0039] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 160° C. for 30 minutes. After the reaction was completed, the mixture was cooled to room temperature. Cyclohexane was added to obtain polymer-protected perovskite quantum dots.

[0040] Example 2

[0041] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0042] (1) Preparation of precursor solution: Polymethyl methacrylate with an amino group end-capping molecular weight of 1,000,000 g / mol was added into a round-bottom flask with lead iodide (PbI2), cesium carbonate (CsCO3), oleic acid, and 1-tetradecene. The mixture was heated to 100° C. in an oil bath and stirred for 5 minutes to mix the mixture evenly to obtain a precursor solution of perovskite.

[0043] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 260° C. for 40 minutes. After the reaction was completed, the mixture was cooled to room temperature. n-hexane was added to obtain polymer-protected perovskite quantum dots.

[0044] Example 3

[0045] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0046] (1) Preparation of precursor solution: Polyacrylamide with a molecular weight of 5,000 g / mol and amino and carboxyl end-capped groups was added to a round-bottom flask with lead chloride (PbCl2), cesium carbonate (CsCO3), and 1-octene. The mixture was heated to 180°C in an oil bath and stirred for 25 minutes to mix well, thereby obtaining a precursor solution of perovskite.

[0047] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 180° C. for 50 minutes. After the reaction was completed, the mixture was cooled to room temperature. Petroleum ether was added to obtain polymer-protected perovskite quantum dots.

[0048] Example 4

[0049] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0050] (1) Preparation of precursor solution: amino-terminated polyisopropylacrylamide with a molecular weight of 10,000 g / mol, lead bromide (PbBr2), cesium carbonate (CsCO3), oleic acid, and 1-dodecene were added to a round-bottom flask, heated to 250°C in an oil bath, and stirred for 30 minutes to mix well to obtain a precursor solution of perovskite.

[0051] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 200° C. for 60 minutes. After the reaction was completed, the mixture was cooled to room temperature. Toluene was added to obtain polymer-protected perovskite quantum dots.

[0052] Example 5

[0053] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0054] (1) Preparation of precursor solution: Carboxyl-terminated polyvinyl chloride with a molecular weight of 50,000 g / mol was added to a round-bottom flask with lead iodide (PbI2), cesium carbonate (CsCO3), oleylamine, and 1-dodecene. The mixture was heated to 300°C in an oil bath and stirred for 15 minutes to mix the mixture evenly to obtain a precursor solution of perovskite.

[0055] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 260° C. for 60 minutes. After the reaction was completed, the solution was cooled to room temperature. Polymer-protected perovskite quantum dots were obtained by adding dioxane.

[0056] Example 6

[0057] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0058] (1) Preparation of precursor solution: Polyethylene with amino group end-capping and molecular weight of 100,000 g / mol was added into a round-bottom flask with lead chloride (PbCl2), cesium carbonate (CsCO3), oleic acid and 1-octadecene. The mixture was heated to 250°C in an oil bath and stirred for 10 minutes to mix the mixture evenly to obtain a precursor solution of perovskite.

[0059] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 120° C. for 45 minutes. After the reaction was completed, the solution was cooled to room temperature. Tetrahydrofuran was added to obtain polymer-protected perovskite quantum dots.

[0060] Example 7

[0061] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0062] (1) Preparation of precursor solution: Polyvinyl alcohol with a molecular weight of 200,000 g / mol and carboxyl and amino groups capped was added to a round-bottom flask with lead bromide (PbBr2), cesium carbonate (CsCO3), and 1-eicosene. The mixture was heated to 140°C in an oil bath and stirred for 15 minutes to mix well, thereby obtaining a precursor solution of perovskite.

[0063] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 140° C. for 50 minutes. After the reaction was completed, the solution was cooled to room temperature. Carbon disulfide was added to obtain polymer-protected perovskite quantum dots.

[0064] Example 8

[0065] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0066] (1) Preparation of precursor solution: Polyvinyl pyridine with a molecular weight of 500,000 g / mol and carboxyl and amino end-capped was added to a round-bottom flask with lead iodide (PbI2), cesium carbonate (CsCO3), and 1-tetradecene. The mixture was heated to 240°C in an oil bath and stirred for 20 minutes to mix well to obtain a precursor solution of perovskite.

[0067] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 180° C. for 35 minutes. After the reaction was completed, the mixture was cooled to room temperature. Ethyl acetate was added to obtain polymer-protected perovskite quantum dots.

[0068] Example 9

[0069] A simple method for preparing long-lasting and stable polymer perovskite quantum dots is prepared as follows:

[0070] (1) Preparation of precursor solution: amino-terminated polyamide with a molecular weight of 1,000,000 g / mol, lead bromide (PbBr2), cesium carbonate (CsCO3), and 1-hexadecene were added to a round-bottom flask, heated to 280° C. in an oil bath, and stirred for 18 minutes to mix well to obtain a precursor solution of perovskite.

[0071] (2) Preparation of perovskite quantum dots: The precursor solution in step (1) was transferred to a hydrothermal reactor and reacted at 240° C. for 45 minutes. After the reaction was completed, the mixture was cooled to room temperature. Polymer-protected perovskite quantum dots were obtained by adding chloroform.

Claims

1. A simple method for preparing perovskite quantum dots with long-term polymer protection, characterized in that: The steps include: (1) Preparation of precursor solution: terminal functionalized polymer is mixed with lead halide (PbX2, X = Br, Cl, I), cesium carbonate CsCO3, and olefin, and then heated and stirred to obtain a precursor solution of perovskite. (2) Preparation of perovskite quantum dots: The precursor solution in step (1) is transferred to a hydrothermal reactor, and the reaction is continued for a period of time under high temperature and high pressure. After the reaction is completed, the solution is cooled to room temperature. A non-polar solvent is added to obtain polymer-protected perovskite quantum dots.

2. The preparation method according to claim 1, characterized in that The terminal functionalized polymer in step (1) contains a carboxyl group (-COOH) or an amino group (-NH2), or both, at its terminal.

3. The preparation method according to claim 1, characterized in that: The molecular weight of the polymer in step (1) is 500 to 1,000,000 g / mol.

4. The preparation method according to claim 1, characterized in that: The solvent in step (1) is an olefin organic compound.

5. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in step (1) is 100 to 300° C., and the heating and stirring time is 5 to 30 minutes.

6. The preparation method according to claim 1, characterized in that: The reaction temperature in step (2) is 120 to 260° C., and the reaction time is 30 to 60 minutes.

7. The preparation method according to claim 1, characterized in that: The non-polar solvent added in step (2) is selected from one of n-hexane, cyclohexane, petroleum ether, carbon disulfide, dichloromethane, chloroform, toluene, benzene, ethyl acetate, dioxane and tetrahydrofuran.

8. A perovskite quantum dot prepared according to the preparation method of claim 1, characterized in that: When stored at room temperature for 60 days, or immersed in a polar solvent (such as water, ethanol, etc.) for 15 days, or placed in a high temperature environment of 100°C for 30 days, the fluorescence intensity decreases by 0-50%.

9. A perovskite quantum dot prepared according to the preparation method of claim 1, characterized in that: Can be dispersed evenly in polymer matrix without local agglomeration. The self-assembly property can be used to prepare self-supporting ordered array films, or it can be mixed with other polymers and co-assembled into ordered structure materials.

10. An application of the polymer long-lasting stable perovskite quantum dots prepared by the method of claim 1, characterized in that: It can be used in photovoltaic power generation, lasers, fluorescence imaging, light-emitting diodes and other fields.